Strategy development in order to growth for càftan muslim fashion wear - Jawwas, Chaulla; Rudy Sirait, Socrates (The Indonesian Journal of Business Administration, 2016)
Abstract - In today’s global competitive marketplace, style for the modern Muslim woman is evolving. Being a country with the largest Muslim population in the world, Indonesian creative industries in Muslim fashion is quite strong and continues to grow rapidly. Additionally, it was challenging to stay in fashion industry if the player doesn’t have any differentiation. CÀFTAN is a form of creativity from Indonesian young people in Muslim fashion wear, which serves customers with the products of women cloths that is unique and fashionable. Along with the development of Muslim fashion wear as well as technology, the demand and revenue also increased for CÀFTAN. However, without a good strategy formulation causes unstable income and can’t achieve the target demand. Follow with the fast-changing environment, many competitors are increasing with different strategy. To improve the performance and be sustainable in the business, CÀFTAN needs to build an appropriate strategy. Strategy formulation process is done by analyzing the external and internal factors that are affected the business. The both factors were formed by data from observation, interviews and questionnaires. CÀFTAN is using Porter’s generic strategy as a frame work to outline the three major strategic options to achieve a sustainable competitive advantage. The strategic differentiation is to determine the tactic differentiation by using 7p marketing mix as a frame work to achieve its competitive advantages and value for the customers. In sales promotion, the strategy is used to determine the marketing strategic for CÀFTAN. Business model canvas used to determine the strategic implementation that was suitable for the company. The author recommends CÀFTAN to use focus differentiation strategy in product and service with product development, improving system operations, creating marketing campaign and cost efficiency to improve its Muslim fashion business in order to capture the market and greater profits as well as improving the company’s competitive position.  Keywords: Muslim Fashion Wear, CÀFTAN, Business Strategy, Strategic Differentiation, Business Model Canvas.